2012
DOI: 10.1590/s1415-47572012005000052
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity assessment of Copaiba oil and its fractions in Swiss mice

Abstract: Copaiba oil-resin, extracted from the trunk of Copaifera, and traditionally used in folk medicine in the treatment of various disorders, has been shown to be an effective antiinflamatory, antitumor, antitetanus, antiseptic and anti-blenorrhagea agent. As, there are few studies evaluating its genotoxicity, this aspect of the commercial oil-resin, and its volatile and resinous fractions, were evaluated in mice by comet assay and micronucleus (MN) test. A single dose of oil resin, volatile or resin fractions (500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…Importantly, the absence of genotoxicity and mutagenicity to mice, administered with acute single doses up to 2 g/Kg of copaiba oil or its volatile and nonvolatile fractions, has been demonstrated using the comet assay as well as by the absence of any increase in the frequency of micronuclei of bone marrow and peripheral blood cells [47]. Moreover, oral treatment with whole C. martii oil reduces L. amazonensis lesions in mice [19].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the absence of genotoxicity and mutagenicity to mice, administered with acute single doses up to 2 g/Kg of copaiba oil or its volatile and nonvolatile fractions, has been demonstrated using the comet assay as well as by the absence of any increase in the frequency of micronuclei of bone marrow and peripheral blood cells [47]. Moreover, oral treatment with whole C. martii oil reduces L. amazonensis lesions in mice [19].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has evaluated the effect of C. langsdorffii oil‐resin in endometriotic foci of rats, finding significant results, including reduction in lesion size [39]. In addition, Almeida and colleagues[40] examined the genotoxicity in mice of commercial copaiba oil‐resin and its fractions, and observed that the oil‐resin and its volatile and resinous fractions are not genotoxic or mutagenic to these animals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, oral administration of CopNEC-AmB decreased its nephrotoxicity as the plasma creatinine level was reduced (data not shown) compared with that after plain AmB. It was also reported in literature that acute single doses of Cop up to 2 g·kg −1 do not cause genotoxic and mutagenic effects in mice (Almeida et al, 2012).…”
Section: Figurementioning
confidence: 52%